2011
DOI: 10.1057/omj.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

When research setting is important: the influence of subordinate self-esteem on reactions to abusive supervision

Abstract: In this paper, we argue that the conflicting theoretical views regarding the role that self-esteem plays in the decision to become aggressive can be explained by the particular research methodology used. Specifically, we examine how individuals respond to a perceived abusive supervisor in two settings: (1) using scenarios and (2) in a field study. Results indicate that individuals with high selfesteem are more likely to become aggressive in response to an abusive supervisor in settings where they are asked wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…The final theoretical contribution of the study is that OBSE does not have a moderation role on the relationship between abusive supervision and job alienation. The studies, which were implemented in the other industries, indicate that OBSE has a moderator role on the relationships between negative incidents and experiences confronted by employees and their behaviors (Kiazad et al, 2010;Burton et al, 2011). Unlike the previous researches, this study demonstrates that OBSE does not have a moderator role.…”
Section: Theoretical Contributionscontrasting
confidence: 69%
See 1 more Smart Citation
“…The final theoretical contribution of the study is that OBSE does not have a moderation role on the relationship between abusive supervision and job alienation. The studies, which were implemented in the other industries, indicate that OBSE has a moderator role on the relationships between negative incidents and experiences confronted by employees and their behaviors (Kiazad et al, 2010;Burton et al, 2011). Unlike the previous researches, this study demonstrates that OBSE does not have a moderator role.…”
Section: Theoretical Contributionscontrasting
confidence: 69%
“…To investigate the moderating role of self-esteem between the negative behaviors that an employee is exposed to and his/her reactions to these behaviors, the Behavioral Plasticity Theory can provide a highly effective background (Pierce et al, 1993;Hui & Lee, 2000;García-Cabrera & García-Barba Hernández, 2014;Ekrot et al, 2016). Employees with low OBSE are more defenseless against the negative incidents they are exposed to and the unfavorable experiences they have in the organization (Burton et al, 2011;Vogel & Mitchell, 2017). The Behavioral Plasticity Theory (Brockner, 1983(Brockner, , 1988 claims that employees with lower self-esteem are more vulnerable and sensitive to negative incidents than the ones with higher levels of selfesteem are.…”
Section: Moderating Effect Of Obsementioning
confidence: 99%
“…In an interesting variation on the study of the abuse–retaliation relationship Burton, Hoobler, and Kernan () examined how the research setting impacts subjects' reports of aggressive responses to abuse. Using a hypothetical scenario design, the authors found that subjects with high self‐esteem reported a strong willingness to engage in (hypothetical) aggressive responses.…”
Section: Abusive Supervision Research (2008–2012)mentioning
confidence: 99%
“…A wide range of active (i.e., outwards directed / high energy) versus passive (i.e., more inwards directed / low energy) behaviors have been studied as being consequences of destructive forms of leadership. When it comes to active behaviors, followers have been shown to respond with aggression (Burton et al, 2011; Burton & Hoobler, 2011; Brees et al, 2014; Carleton et al, 2016; Dupré et al, 2006; Lian et al, 2014; Pradhan et al, 2019a; Richard et al, 2018), counterproductive work behavior (Akram et al, 2019; Brender-Ilan & Sheaffer, 2019; Chu, 2014; Duffy et al, 2006; Goswami et al, 2019; Ju et al, 2019; Low et al, 2019; Ogunfowora, 2013; Shoss et al, 2013; Simon et al, 2015; Watkins et al, 2019; Yang et al, 2019), deviance (Avey et al, 2015; Javed et al, 2019; Mackey et al, 2015; Mawritz et al, 2017; Rice et al, 2020a; Schmid et al, 2019; Thoroughgood et al, 2018; Valle et al, 2019; Vogel et al, 2016; Wang & Jiang, 2014), or reactance (Bligh et al, 2007; Goswami et al, 2015; Haggard & Park, 2018; Liu et al, 2010; Tepper et al, 2001). Destructive forms of leadership have also been linked with passive follower behaviors such as withdrawal (Allen et al, 2016; Chi & Liang, 2013; Huang et al, 2020; Kim et al, 2019; Mawritz et al, 2014; Wei & Si, 2013), turnover / turnover intention (Agarwal, 2019; Ogunfowora et al, 2019; Palanski et al, 2014; Pradhan et al, 2018; Ramdeo & Singh, 2019; Rice et al, 2020a; Schmid et al, 2018; Pradhan et al, 2019a;…”
Section: Leader Antecedents and Follower Consequences Of Destructive ...mentioning
confidence: 99%